1997
DOI: 10.1088/0031-8949/56/6/021
|View full text |Cite
|
Sign up to set email alerts
|

Plasma focus characteristics using stainless steel anode

Abstract: In a low energy (2.3 kJ) Mather-type plasma focus with stainless steel anode, neutron and x-ray emission is investigated by employing time-integrated and time resolved detectors. A neutron yield of 3.5 × 108 is observed, which is almost double the yield when a copper anode is used. It is speculated that a low sputtering yield of the anode material lowers the impurity concentration in the plasma and thus enhances the neutron yield. One may therefore conclude that a proper choice of electrode material is essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…During the last few decades, attempts have been made to enhance neutron yield from a plasma focus by adjusting different parameters such as capacitor energy, operating voltage, circuit inductance, pressure of working gases, material and shape of electrodes, proper selection of the length of the anode and insulator and different machine parameters in addition to normal operating conditions [3][4][5][6][7][8][9][10][11][12]. Plasma focus pulsars are among the cheapest available neutron generators, with unique features of extremely short pulses (hundreds of nanoseconds) that suit a number of interesting applications.…”
Section: Introductionmentioning
confidence: 99%
“…During the last few decades, attempts have been made to enhance neutron yield from a plasma focus by adjusting different parameters such as capacitor energy, operating voltage, circuit inductance, pressure of working gases, material and shape of electrodes, proper selection of the length of the anode and insulator and different machine parameters in addition to normal operating conditions [3][4][5][6][7][8][9][10][11][12]. Plasma focus pulsars are among the cheapest available neutron generators, with unique features of extremely short pulses (hundreds of nanoseconds) that suit a number of interesting applications.…”
Section: Introductionmentioning
confidence: 99%
“…The performance of this device was found to be higher than any other PF apparatus, compared on the empirical scaling law of neutron yield versus pinch current. A remarkable sixfold increase in the average maximum total neutron yield, compared to the similar energy UNU-ICTP Plasma Focus device, 18 was achieved for deuterium at a relatively much higher filling gas pressure of 20 mbar by Koh et al 19 Zakaullah et al 20 reported an increased neutron yield by using stainless steel anode instead of copper anode in a low energy ͑2.3 kJ͒ plasma focus device. Neutron yield of 3.5ϫ 10 8 was recorded by employing time integrated and time resolved detectors, which was almost twice the yield obtained from Cu anode.…”
Section: Effect Of Anode Shape On Correlation Of Neutron Emission Witmentioning
confidence: 99%
“…For this reason, plenty of work has been done on theoretical and experimental dependencies of neutron yield. For instance, the configuration of device, insulator characteristics, shape of the central anode, amount of peak and pinch currents and pressure and voltage values play an important role in obtaining the maximum neutron yield [11][12][13]. Another important point is that spatial scattering of yields is changed by the above-mentioned parameters.…”
Section: Introductionmentioning
confidence: 99%